Revealing the Problem of Deficiencies in the Implementation of Islamic Religious Education Subjects in Indonesian Schools - Citra Aulia Rahmi; Juliani; Iqbal Nur Afazi; Julaiha; Dhea Puja Puspita; Ahmad Dimas Syahputra (Journal of Contemporary Islamic Primary Education, 2024)
Islamic Religious Education (PAI) plays a strategic role in shaping the character and morals of students in schools. However, various obstacles often hinder its optimal implementation. This article aims to analyze the factors causing the suboptimal implementation of PAI in Indonesian schools and propose solutions based on recent literature. Issues such as limited time allocation, inadequate resources, lack of diverse teaching methods, and teachers’ competencies in utilizing technology are comprehensively discussed. Proposed solutions include extending learning time, developing teaching materials, conducting teacher training, adopting interactive teaching methods, and fostering parental and community support. This study is expected to serve as a reference for improving the quality of PAI learning in schools.